Pelvic floor muscle activity during coughing and valsalva maneuver in continent women and women with stress urinary incontinence: a systematic review - Martinez, Renata Ferreira Lobo; Sato, Tatiana de Oliveira; Silva, Jordana Barbosa da; Figueiredo, Vilena Barros de; Avila, Mariana Arias; Driusso, Patricia (Universidade Federal de São Carlos, 2023)
Pelvic floor muscle (PFM) activation during efforts activities may predispose to urinary loss. However, there is unclear evidence on the behavior of PFM during situations of coughing and Valsalva maneuver. Objectives: Hence, the present review aimed to evaluate the current evidence on electromyographic (EMG) activity of PFM during coughing and Valsalva maneuver in continent women and women with stress urinary incontinence (SUI). Methods: The databases EMBASE, PubMed, Science Direct, Scopus and were searched up to August, 2021. Two independent reviewers conducted the selection process based on titles, abstracts, and full-text reading. In addition, studies reporting PFM EMG activity during coughing and/or the Valsalva maneuver with surface EMG were included. The methodological quality of the primary studies was assessed through the checklist proposed by the Joanna Briggs Institute for cross-sectional studies. Results: Seven cross-sectional studies were included in this review, four of which were on PFM activation of continent women, while the other three compared continent women versus women with SUI. During both Valsalva maneuver and coughing, an increase of PFM EMG activity compared to rest was observed for continent women and women with SUI. Limitations of the present systematic review are that comparison among studies and a meta-analysis were not possible due to heterogeneity of EMG techniques and devices used. Conclusions: Coughing and Valsalva maneuver lead to an increase in PFM electrical activity compared to rest. This increase was more prominent in women with SUI during Valsalva, with no differences during coughing.
Keywords: Fisioterapia; Assoalho pélvico; Saúde da mulher; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL